Deep Learning and Application in Elementary Schools: an Exploration of Learning Practices - Bagus Cahyanto (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This paper aims to explore the implementation of the deep learning approach in learning science for grade IV at SDN 2 Ringinanom Ponorogo. This study uses a qualitative case study approach with data collection techniques using interviews, observations, and documentation studies. The researcher uses interactive data analysis by Miles, Huberman, and Saldana which includes data reduction, data presentation, and verification and drawing conclusions. The results of the study indicate that the implementation of the deep learning approach at SDN 2 Ringinanom was carried out by integrating three main principles, namely meaningful learning, mindful learning, and joyful learning. These three principles have been proven to be able to create meaningful learning experiences by strengthening aspects of understanding, application, and reflection. The application of deep learning also has an impact on improving learning outcomes and student involvement in learning. These findings provide an important contribution by offering pedagogical innovations that focus on cognitive achievement as well as the development of students' affective, psychomotor and social dimensions. The results of this study also confirm that the application of deep learning has been proven to be able to create a more active and participatory learning experience to develop the knowledge and skills needed by students in the future.